2005
DOI: 10.1111/j.1744-7909.2005.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Genetic Structure of Sclerotinia sclerotiorum (Lib.) de Bary Populations from Different Regions and Host Plants by Random Amplified Polymorphic DNA Markers

Abstract: The genetic diversity and genetic structure of a population of isolates of Sclerotinia sclerotiorum (Lib.) de Bary from different regions and host plants were investigated using the random amplified polymorphic DNA (RAPD) method with 20 random decamer primer pairs in order to provide some information on the phylogenetic taxa and breeding for resistance to sclerotinia stem rot. A minimum of three and a maximum of 15 unambiguously amplified bands were generated, furnishing a total of 170 bands ranging in size fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 14 publications
1
43
0
Order By: Relevance
“…During the study, bigger sizes of sclerotia were observed in the same morphological group and genetic cluster. Sun et al (2005) compared S. sclerotiorum Table 3. Similarity matrix generated through Jacquard coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…During the study, bigger sizes of sclerotia were observed in the same morphological group and genetic cluster. Sun et al (2005) compared S. sclerotiorum Table 3. Similarity matrix generated through Jacquard coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al (2005) reported that the relationship between Canadian and Polish populations of S. sclerotiorum was very close, although the geographic distance between them was large. Also, Li et al (2009) analyzed five populations of S. sclerotiorum isolated from sunflower in three countries, Mongolia, in China, Canada, and the United Kingdom.…”
Section: Sclerotinia Sclerotiorum Populations In Asia Europe and Ocementioning
confidence: 99%
“…Several reports concerning the population structure of S. sclerotiorum in Asia are available: Iran (Hemmati et al, 2009;Barari et al, 2010Barari et al, , 2011Colagar et al, 2010;Karimi et al, 2011), Jordan (Colagar et al, 2010); Pakistan (Akram et al, 2008), Turkey (Mert-Türk et al, 2007;Yanar and Onaran, 2011) and China (Sun et al, 2005;Li et al, 2008Li et al, , 2009Chen et al, 2010). Different vegetable crop fields were analyzed in these studies and most authors came to the general conclusion that populations exist somewhere in the spectrum between sexual outcrossing and clonal.…”
Section: Sclerotinia Sclerotiorum Populations In Asia Europe and Ocementioning
confidence: 99%
See 1 more Smart Citation
“…In general, clonal reproduction has been shown to be predominant in temperate climate regions, whereas sexual recombination contributes to population structure in milder climates (Cubeta et al, 1997;Kohli and Kohn, 1998;Carpenter et al, 1999;Atallah et al, 2004;Sun et al, 2005;Malvárez et al, 2007;Arbaoui et al, 2008). Individual isolates are classified into clonal lineages by the use of two or more independent markers, such as mycelial compatibility groups (MCGs), DNA fingerprinting, or microsatellites (Kohn et al, 1991;Carbone et al, 1999;Sirjusingh and Kohn, 2001;Hambleton et al, 2002;Auclair et al, 2004).…”
Section: Introductionmentioning
confidence: 99%